An Investigation Into the Interplay Between Lecturers' Beliefs About Teaching, Learning, Assessment And The College's Conceptual Framework. - Dlamini, Albert Malaba (2020)
This study is a case study, carried out at a Teachers' College in Zimbabwe. It was conducted to investigate the interplay between lecturers' pedagogical beliefs and the College's conceptual framework. A purposive sample of eight participants was drawn from across subject areas to try and make it as representative as possible. As the purpose of the study was to explore lecturers' pedagogical beliefs and understand how these inform their pedagogical practices, I preferred to use a qualitative case study design, considered to be an appropriate methodology for this type of study.To collect data I used multi-methods which included participant observation, lesson observations, in-depth interviews and focus group discussions. In the data analysis process, I used the inductive approach, characterised by systematic categorisation of data from all the 5 data sets; and authentic themes emerged from the data. The findings of this study revealed that, some lecturers held traditional teacher-centred pedagogical beliefs, while other held the interactive, learner-centred beliefs. About learning, participants held different views about how students learn: some believed that students learn by receiving knowledge from the teacher; while others believed students learn by interacting, sharing ideas and constructing their own understanding and knowledge. However, during lesson observations, 6 lecturers used the traditional teacher-centred teaching approaches, while only 2 used the interactive learner-centred approaches. About assessment, participants, while they believed assessment can play a role in teaching/learning process; the College culture of assessment was a constraining factor as it has no room for alternative forms of assessment. The findings also show that lecturers are not aware of the theoretical and educational significance of the College's conceptual framework. As a result lecturers do not model their pedagogical practices to try and achieve or meet the vision of the college; as articulated by the College's conceptual framework.